(untitled) (Journal of Technology and Operations Management, 2017)
Service quality (SERVQUAL) is one method that can be used to measure customer satisfaction for services that have been received that is by comparing the level of perception and expectations. Lean, six sigma is a method or technique for controlling and improving the quality of which is a dramatic breakthrough in the field of quality and is always oriented to customer satisfaction with a measurement target of sigma quality level. Integration SERVQUAL and Lean Six Sigma methods aims to SERVQUAL measurement results were analysed is to determine the critical variables, followed by calculation of DPMO and sigma value of the critical variables that can be known variables that priority improvements